Medical-surgical qualifications mid-six century : the "ministrantes" (health officers) - Isidoro Jiménez Rodríguez (Universidad de Alicante, 2012)
Framed within the professional field of "nursing", there have been along the centuries various figures who performed several functions. The present study deals with the approach to one of them: the ministrante (Health Officer/Officier de santé), whose most paramount aspect is that of their technical-surgical tone. Professional attributions and inter-relationship with some other health professions together with different circumstances that motivated their onset are considered here.